2004
DOI: 10.4141/p03-118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial N reserve status and residual leaf area after cutting on leaf area and organ establishment during regrowth of alfalfa

Abstract: . 2004. Effects of initial N reserve status and residual leaf area after cutting on leaf area and organ establishment during regrowth of alfalfa. Can. J. Plant Sci. 84: 1059-1066. Nitrogen reserves in remaining organs and residual leaf area after cutting have long been recognized as key factors during alfalfa (Medicago sativa L.) regrowth. The present work examined which morphological components were influenced by contrasting initial N status and residual leaf area during 29 d of regrowth after cutting at 15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The model uses a linear interpolation to compute partitioning change as decimal V-stage progresses. Difficulties in adjusting the partitioning for both phases due to the lack of observed leaf, stem, and root fraction were managed by extrapolating data from literature (Stavarache et al, 2012;Teixeira et al, 2007) and comparing them to the simulated data on leaf percentage, total biomass, roots, and storage (crown-taproot) (Meuriot et al, 2004;Simon et al, 2004).…”
Section: Dry Matter Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The model uses a linear interpolation to compute partitioning change as decimal V-stage progresses. Difficulties in adjusting the partitioning for both phases due to the lack of observed leaf, stem, and root fraction were managed by extrapolating data from literature (Stavarache et al, 2012;Teixeira et al, 2007) and comparing them to the simulated data on leaf percentage, total biomass, roots, and storage (crown-taproot) (Meuriot et al, 2004;Simon et al, 2004).…”
Section: Dry Matter Partitioningmentioning
confidence: 99%
“…Observed percent leaf values of harvested herbage were extrapolated from Stavarache et al (2012) study in Romania for three cuts during the first season, and those values ranged between 42 and 61%. In the study of Simon et al (2004), the leaf percentage varied between 50 and 53% under different N fertilization and residual leaf area treatments. In our experiments, the simulated percent leaf was around 70% (the average of the 6 experiments).…”
Section: Dry Matter Partitioningmentioning
confidence: 99%
“…biomass of leaves, young stems and remnant leaf area) in plants cut at 100 mm of height. In this regard, numerous studies have shown the positive relationship between remaining green biomass and subsequent aerial growth in lucerne plants (Leach, 1969;Hodgkinson, 1973;Simon et al, 2004;Meuriot et al, 2005;Favero et al, 2008).…”
Section: Discussionmentioning
confidence: 99%